(untitled) (Journal of Health, Population and Nutrition, 2009)
Achieving Millennium Development Goal 5 in Bangladesh calls for an appreciation of the evolution of maternal healthcare within the national health system to date plus a projection of future needs. This paper assesses the development of maternal health services and policies by reviewing policy and strategy documents since the independence in 1971, with primary focus on rural areas where three-fourths of the total population of Bangladesh reside. Projections of need for facilities and human resources are based on the recommended standards of the World Health Organization (WHO) in 1996 and 2005. Although maternal healthcare services are delivered from for-profit and not-for-profit (NGO) subsectors, this paper is focused on maternal healthcare delivery by public subsector. Maternal healthcare services in the public sector of Bangladesh have been guided by global policies (e.g. Health for All by the Year 2000), national policies (e.g. population and health policy), and plans (e.g. five- or three-yearly). The Ministry of Health and Family Welfare (MoHFW), through its two wings-Health Services and Family Planning-sets policies, develops implementation plans, and provides rural public-health services. Since 1971, the health infrastructure has developed though not in a uniform pattern and despite policy shifts over time. Under the Family Planning wing of the MoHFW, the number of Maternal and Child Welfare Centres has not increased but new services, such as caesarean-section surgery, have been integrated. The Health Services wing of the MoHFW has ensured that all district-level public-health facilities, e.g. district hospitals and medical colleges, can provide comprehensive essential obstetric care (EOC) and have targeted to upgrade 132 of 407 rural Upazila Health Complexes to also provide such services. In 2001, they initiated a programme to train the Government’s community workers (Family Welfare Assistants and Female Health Assistants) to provide skilled birthing care in the home. However, these plans have been too meagre, and their implementation is too weak to fulfill expectations in terms of the MDG 5 indicator-increased use of skilled birth attendants, especially for poor rural women. The use of skilled birth attendants, institutional deliveries, and use of caesarean section remain low and are increasing only slowly. All these indicators are substantially lower for those in the lower three socioeconomic quintiles. A wide variation exists in the availability of comprehensive EOC facilities in the public sector among the six divisions of the country. Rajshahi division has more facilities than the WHO 1996 standard (1 comprehensive EOC for 500,000 people) whereas Chittagong and Sylhet divisions have only 64% of their need for comprehensive EOC facilities. The WHO 2005 recommendation (1 comprehensive EOC for 3,500 births) suggests that there is a need for nearly five times the existing national number of comprehensive EOC facilities. Based on the WHO standard 2005, it is estimated that 9% of existing doctors and 40% of nurses/midwives were needed just for maternal healthcare in both comprehensive EOC and basic EOC facilities in 2007. While the inability to train and retain skilled professionals in rural areas is the major problem in implementation, the bifurcation of the MoHFW (Health Services and Family Planning wings) has led to duplication in management and staff for service-delivery, inefficiencies as a result of these duplications, and difficulties of coordination at all levels. The Government of Bangladesh needs to functionally integrate the Health Services and Family Planning wings, move towards a facility-based approach to delivery, ensure access to key maternal health services for women in the lower socioeconomic quintiles, consider infrastructure development based on the estimation of facilities using the WHO 1996 recommendation, and undertake a human resource-development plan based on the WHO 2005 recommendation. Key words: Maternal health; Maternal health services; Rural health services; Bangladesh doi: 10.3329/jhpn.v27i2.3326 J Health Popul Nutr 2009 April;27(2):124-138